Performa Kualitas Produk, Citra Merek dan Persepsi Harga dalam Mempengaruhi Keputusan Pembelian (Studi pada Konsumen Mobil Honda Brio Satya di Kota Semarang) - Muhammad Farikhin; Rokh Eddy Prabowo (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2019)
This study aims to analyze each product's quality performance, brand image, and price perception in influencing the purchase decision of a Honda Brio Satya car. The population is the buyers of the Honda Brio Satya car with a sample of 100 people determined by the non probability sampling method. To obtain primary data, a questionnaire was used, while secondary data was obtained by using the library method. The primary data collected was then processed with the help of the SPSS Version 19.0 program. Based on the results of SPSS Version 19.0 obtained information, that the research instrument was declared valid and reliable. Regression results show that not all variables have a positive sign. Variables that are positive are product quality and brand image, while price perception variables are negative. Based on the F test, all variables simultaneously have a significant effect on purchasing decisions. T test results showed that the performance of the product quality variable did not influence the purchase decision, the brand image variable had a positive and significant effect on the purchase decision, and the price perception variable did not affect the purchasing decision of the Honda Brio Satya car